EXPERIMENTAL CALCULATION OF THREE DIMENSIONED (3D) CURRENT MODEL IN VAN PHONG BAY - Long, Bui Hong; Chung, Tran Van (Vietnam Journal of Marine Science and Technology, 2006)
EXPERIMENTAL CALCULATION OF THREE DIMENSIONED (3D) CURRENT MODEL IN VAN PHONG BAY